PENTINGNYA EDUKASI TINDAKAN ASUSILA KEPADA ANAK DIBAWAH UMUR - Rizky Moejiono; Siti Maizul Habibah (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2024)
The need for legal protection for children is very important for society, technological developments have also led to an increase in various crimes that can happen to anyone, including children. In order for every child to be responsible for defending his nation and state in the future, every child must have the widest opportunity to grow and develop optimally both physically, mentally and socially. However, the best interests of the child must always come first, especially if the child is a victim of sexual abuse. Because supervision of children is very important both in terms of maintaining and quality of life and the future of the nation, crimes of sexual violence against children must be dealt with immediately and the rights of children as victims of crime must be addressed. protected Based on the research results it can be understood that the legal protection of child victims of sexual crimes is based on law. Factors causing the occurrence of sexual crimes against minors are internal factors such as weakening of faith/trust, psychosocial disturbances and sexual disturbances. External factors include moral values and customs, poverty/economic factors, the mass media. Precautions for minor sex crimes, ie. environmental socialization, legal counseling for schools and the community. Keywords: Socialization, Sexual Violence, Minors.